2020
DOI: 10.3390/molecules25204757
|View full text |Cite
|
Sign up to set email alerts
|

Potential Beneficial Effects of Extra Virgin Olive Oils Characterized by High Content in Minor Polar Compounds in Nephropathic Patients: A Pilot Study

Abstract: Extra virgin olive oil (EVOO) is a lipid food, which constitutes a pillar of the Mediterranean diet. A high number of scientific data have demonstrated that it exerts a variety of beneficial effects on human health due to its peculiar chemical composition including fatty acids (98–99%) and other active compounds even if found in a very low percentage (1–2%). Among them, minor polar compounds (MCPs), represented mainly by phenolic compounds, are relevant for their healthy properties, as stated by the European F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…Moreover, it should be noted that the term “PBD” does not necessarily mean “healthy”, since there is evidence that certain non-animal-origin food such as refined cereals, snacks, pastries or sugary drinks are harmful to health [ 32 ]. PBD to be defined as “healthy” must promote the intake of whole grains, fruit, vegetables, legumes and non-hydrogenated vegetable oils, such as extra-virgin olive oil (EVOO) [ 33 , 34 , 35 ]. Finally, the substitution of certain animal-origin food helps in reducing the intake of harmful components present in red and processed meats, such as excessive sodium, heme iron, nitrates and nitrites, which increase the risk of CVDs and MetS onset [ 33 ].…”
Section: Plant-based Dietary Patterns and Environmental Impactsmentioning
confidence: 99%
“…Moreover, it should be noted that the term “PBD” does not necessarily mean “healthy”, since there is evidence that certain non-animal-origin food such as refined cereals, snacks, pastries or sugary drinks are harmful to health [ 32 ]. PBD to be defined as “healthy” must promote the intake of whole grains, fruit, vegetables, legumes and non-hydrogenated vegetable oils, such as extra-virgin olive oil (EVOO) [ 33 , 34 , 35 ]. Finally, the substitution of certain animal-origin food helps in reducing the intake of harmful components present in red and processed meats, such as excessive sodium, heme iron, nitrates and nitrites, which increase the risk of CVDs and MetS onset [ 33 ].…”
Section: Plant-based Dietary Patterns and Environmental Impactsmentioning
confidence: 99%
“…Major causes include metabolic acidosis, dialysis therapy, and typical low-grade chronic inflammatory status [ 40 , 41 ]. These elements together result in an increase in protein degradation and in a reduction in protein synthesis, producing a negative nitrogen balance ( Figure 2 ) [ 42 , 43 ].…”
Section: Sarcopenia In Chronic Kidney Diseasementioning
confidence: 99%
“…A recent in vitro study by Vamanu et al [305], demonstrated that Curcuma longa extract, particularly rich in curcumin, changes the gut microflora composition of hypertensive patients through the increased release of SCFAs thus, in turn, enhances the Enterobacteriaceae and decreases Bacteroidetes-Prevotella-Porphyromonas genera. Several studies speculate that the modulation of metabolic pattern producing SCFAs may represent an innovative approach to counteract pathological conditions, such as MetS, chronic kidney disease, and AH, characterized by a low-grade inflammatory status [44,45,49,74,261,306]. In this perspective, the most SCFA studied is represented by butyric acid.…”
Section: Effects Of Natural Bioactive Compounds On Gut Microbiota Metmentioning
confidence: 99%
“…In recent years, EVOO has attracted particular scientific interest for its antioxidant and anti-inflammatory properties. EVOO has beneficial properties that counteract the onset and progression of CDNCDs [ 259 , 260 , 261 , 272 , 273 ]. These properties seem to be exerted by the antioxidant and anti-inflammatory action of the polyphenols that it contains, in particular hydroxytyrosol and oleocanthal.…”
Section: Possible Effects Of Natural Bioactive Compounds In Metabomentioning
confidence: 99%